In vivo and in vitro study of fungal presence and growth on three tissue conditioning materials on implant supported complete denture wearers - ÖZKAN, YASEMİN (Blackwell Publishing Ltd, 1998)
In this study three type of tissue conditioning materials were used in vitro and in vivo to investigate the presence and growth of Candida albicans, considered to be the pathogenic member of the genus. In vitro test results of different tissue conditioners showed that they have a tendency to have an inhibiting effect on C. albicans at the third day of incubation. For the in vivo tests tissue conditioners were placed in existing maxillary prosthesis of 21 patients who had been treated with endosseous dental implants (seven in each group). The results showed that yeast forms were observed after 3 days in two patients' dentures which were relined with Fitt. Yeasts forms were also seen in three patients' dentures after 6 days, two of them relined with Fixo-gel and the other one relined with Visco-gel. The hyphal form of Candida was seen in four patients' dentures, relined with Fitt, and also in three patients' dentures, relined with Fixo-gel and Visco-gel. © 1998 Blackwell Science Ltd.